FAKTOR-FAKTOR YANG MEMENGARUHI FIRM VALUE DIMODERASI OLEH FIRM SIZE - Sulistio, Shania; Yanti, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to find out how profitability, leverage, liquidity, activity, and cash holding affect firm value with firm size as the moderating variable which are recorded on the Indonesia Stock Exchange during 2017-2021. The sample was collected using a method called purposive sampling and the validated data was 60 companies. The technique used to process the data uses multiple regression analysis aided by the Eviews version 13 program. The results of this study show that profitability, liquidity, and firm size do not affect firm value. Meanwhile, leverage, activity, and cash holding affect firm value. Firm size cannot moderate its effect on firm value. The implication of this research is the need to improve the quality of management in the company which can increment firm value, so that it can provide positive signs for investors.